2014
DOI: 10.4236/jfcmv.2014.23012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Aerodynamic Sound Source around a Circular Cylinder by Particle Image Velocimetry

Abstract: The purpose of this paper is to propose a sound localization method as an alternative of the time-resolved particle image velocimetry (PIV) system for detecting the aerodynamic sound source of a circular cylinder in a uniform flow. The sound source intensity of a circular cylinder in a uniform flow is evaluated by measuring the time-derivative of instantaneous velocity field in the flow field using a pair of planar PIV system. It allows the visualization of the sound source intensity distribution, which is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…According to the vorticity contours, as the vortices are shed alternately into the wake, the angle of the separated shear layer with the horizontal cylinder tangent line varies with time and the separated shear layer interacts with the cylinder surface alternately. The time-dependent variation of dilatation around the flow separation point suggests that the pressure fluctuation around the flow separation point is the sound source previously detected by Oguma et al (2013) and Oguma, Yamagata & Fujisawa (2014).…”
Section: Flow Features and Flow Validationmentioning
confidence: 56%
“…According to the vorticity contours, as the vortices are shed alternately into the wake, the angle of the separated shear layer with the horizontal cylinder tangent line varies with time and the separated shear layer interacts with the cylinder surface alternately. The time-dependent variation of dilatation around the flow separation point suggests that the pressure fluctuation around the flow separation point is the sound source previously detected by Oguma et al (2013) and Oguma, Yamagata & Fujisawa (2014).…”
Section: Flow Features and Flow Validationmentioning
confidence: 56%
“…The experiment was performed in an acoustic open-jet wind tunnel, which has been described in Ref. [21].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Although these experimental methods allow the localization of the aerodynamic sound sources, the last two methods can simultaneously evaluate the sound source and velocity field, which is useful for understanding the generation mechanism of aerodynamic sound. Recently, a method using two sets of standard PIV systems has been reported for the localization of the sound source from a circular cylinder in a uniform flow [21]. This method allows the evaluation of the sound source without relying on the high-speed PIV system; thus, it is well suited for the detection of the sound source from a bluff body of complex geometry for industrial applications, though the applications have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] The sound source in the flow field was measured experimentally using a combination of microphone measurements and a PIV technique, [19][20][21] and by taking the time-derivative of the velocity field obtained from the PIV. 22 So far, many efforts have been dedicated to analyzing flow structures and aerodynamic sound not only for circular cylinders, but also rectangular cylinders. [23][24][25][26] Fewer studies on the flow structures and aeroacoustics of the D-shaped cylinders have been conducted.…”
Section: Introductionmentioning
confidence: 99%